Joe Celko's Trees and hierarchies in SQL for smarties - Celko, Joe. (Amsterdam ; Boston : Morgan Kaufmann, 2004)
Joe Celko's Trees and Hierarchies in SQL is an intermediate to advanced-level practitioners guide to mastering the two most challenging aspects of developing database applications in SQL. In this book, Celko illustrates several major approaches to representing trees and hierarchies and related topics that should be of interest to the working database programmer. These topics include hierarchical encoding schemes, graphs, IMS, binary trees, and more. This book covers SQL-92 and SQL:1999. Includes graph theory and programming techniques. Running examples throughout the book help illustrate and tie concepts together. Loads of code, available for download from www.mkp.com.
Graphs, trees, and hierarchies -- Adjacency list model -- Path enumeration models -- Nested set model of hierarchies -- Frequent insertion trees -- The linear version of the nested sets model -- Binary trees -- Other models for trees -- Proprietary extensions for trees -- Hierarchies in data modeling -- Hierarchical encoding schemes -- Hierarchical database systems (IMS).
Includes bibliographical references (p. [215]-216).
Keywords: SQL (Computer program language).; Trees (Graph theory); Electronic books